Design and Evaluation of Single and Multi-unit Sustained Release Dosage Forms of Captopril - Ramesh, Dr. K. V. R. N. S. (Asian Journal of Pharmaceutics (AJP), 2017)
Background: Multi-unit dosage forms such as microcapsules and microspheres offer the advantage of better control over the release and lesser chances of dose dumping. This is critical for drugs with high dose, and no comparative study between single and multi-unit forms for controlled release was done previously. Objectives: To explore the utility of using a combination of almond gum and gelucire for preparing sustained–release (SR) matrix tablets. To employ a novel technique of microencapsulating the alginate beads of captopril for SR. Materials and Methods: Almond gum, gelucire (43/01), and ethyl cellulose were the major polymers used. Direct compression and emulsion solvent evaporation methods were employed to prepare the matrix tablets and microcapsules. The prepared products were evaluated for drug release and characterized by scanning electron microscopy, differential scanning calorimetry (DSC), and infrared spectroscopic studies. Accelerated stability study was performed, and drug release was studied before and after stability test. Results and Discussion: Drug release from the matrix tablets could be modified by changing the proportion of gelucire or almond gum in the formulation. The combined use of almond gum and gelucire is found to be more effective in giving a slow, and complete release spread over 12 h. Infrared spectroscopic and DSC studies revealed that there are no interactions of captopril with the various polymers. The microcapsules of alginate beads prepared employing ethyl cellulose are found to be free flowing and had an average size in the range of 750-850 μ. The matrix tablets of captopril are found to be giving more controlled release for a longer period of 12 h compared to the microcapsules. Conclusion: Entrapping the drug in a lipophilic material such as gelucire or beeswax and preparing the calcium alginate microspheres which are subsequently microencapsulated is a promising new approach to obtain the SR of highly water soluble drugs such as captopril.